Digestive proteases in bodies and faeces of the two-spotted spider mite, Tetranychus urticae. (July 2015) - Santamaría, María E.; González-Cabrera, Joel; Martínez, Manuel; Grbic, Vojislava; Castañera, Pedro; Díaz, lsabel; Ortego, Félix
Graphical abstract: Highlights: Cysteine and aspartyl proteases are involved in proteolytic digestion in T. urticae . Legumain-like activity has been characterised for the first time in a phytophagous mite. T. urticae regulates the expression of proteases in response to the ingestion of protease inhibitors. Abstract: Digestive proteases of the phytophagous mite Tetranychus urticae have been characterised by comparing their activity in body and faecal extracts. Aspartyl, cathepsin B- and L-like and legumain activities were detected in both mite bodies and faeces, with a specific activity of aspartyl and cathepsin L-like proteases about 5- and 2-fold higher, respectively, in mite faeces than in bodies. In general, all these activities were maintained independently of the host plant where the mites were reared (bean, tomato or maize). Remarkably, this is the first report in a phytophagous mite of legumain-like activity, which was characterised for its ability to hydrolyse the specific substrate Z-VAN-AMC, its activation by DTT and inhibition by IAA but not by E-64. Gel free nanoLC–nanoESI-QTOF MS/MS proteomic analysis of mite faeces resulted in the identification of four cathepsins L and one aspartyl protease (from a total of the 29 cathepsins L, 27 cathepsins B, 19 legumains and two aspartyl protease genes identified the genome of this species). Gene expression analysis reveals that four cathepsins L and the aspartyl protease identified in the mite faeces, but also two cathepsins B and two legumains that were not detected in the faeces, were expressed at high levels in the spider mite feeding stages (larvae, nymphs and adults) relative to embryos. Taken together, these results indicate a digestive role for cysteine and aspartyl proteases in T. urticae . The expression of the cathepsins B and L, legumains and aspartyl protease genes analysed in our study increased in female adults after feeding on Arabidopsis plants over-expressing the HvCPI-6 cystatin, that specifically targets cathepsins B and L, or the CMe trypsin inhibitor that targets serine proteases. This unspecific response suggests that in addition to compensation for inhibitor-targeted enzymes, the increase in the expression of digestive proteases in T. urticae may act as a first barrier against ingested plant defensive proteins.